Nanopartículas poliméricas associadas ao controle de formigas cortadeiras e busca de novas substâncias naturais com atividade antitumoral - Cazal, Cristiane de Melo (Universidade Federal de São Carlos, 2011)
PART I: Polymeric nanoparticles and bioassay-guided phytochemical investigation of Trichilia elegans e Trichilia catigua (Meliaceae) for the control of leaf-cutting ants Leaf-cutting ants are known as severe agricultural pests. Several compounds have been proposed for their control such as organophosphorus, pyrethroids and sulfluramid insecticides. However, non-target animals and environmental contamination are common problems and therefore new strategies to control these pests have been requested. In this context, this work involved the bioassay-guided study of T. elegans e T. catigua (Meliaceae) and also the development and characterization of three different nanoparticles, containing either ricinine, xanthyletin or rauianin for the control of leaf-cutting ants. Phytochemical investigations from active extracts and fractions have allowed to isolate 23 compounds (3 new), including sterols, coumarins, phenolic compounds, oxazol derivative, flavonoids and limonoids. The compound 3-(4'-hydroxyphenyl)-2-propenoic acid (4''-carboxyl)-phenyl ester (14), from T. elegans, showed high biologic activity against leaf-cutting ants. Additionally, the limonoid cedrelone, from T. catigua, was active against the symbiotic fungus of leaf-cutting ants (L. Leucoagaricus gongylophorus). The solvent displacement technique adopted here showed to be very efficient for the preparation of nanoparticle formulations containing either xanthyletin or rauianin. In addition, a novel method was developed for the encapsulation of ricinine. These natural insecticides were nanoencapsulated for the first time and the results observed here showed a better activity, more water dispersivity and stabilization of nanoparticles if compared to free compounds.
Polymeric nanoparticles for the control of eafcutting ants and search for novel natural substances with antitumor activities
Keywords: Produtos naturais; Nanopartículas poliméricas; Formigas cortadeiras; Antitumoral; Trichilia; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS